Avoidance of vitamin D deficiency to slow the COVID-19 pandemic - Martin Kohlmeier (BMJ Nutrition, Prevention & Health)
Vitamin D deficiency, which impedes good immune function, is common during winter and spring in regions of high latitude. There is good evidence that vitamin D deficiency contributes to the seasonal increase of virus infections of the respiratory tract, from the common cold to influenza, and now possibly also COVID-19. This communication explores key factors that make it more likely, particularly in combination, that individuals are vitamin D deficient. These factors include old age, obesity, dark skin tone and common genetic variants that impede vitamin D status. Precision nutrition is an approach that aims to consider known personal risk factors and health circumstances to provide more effective nutrition guidance in health and disease. In regard to avoiding vitamin D deficiency, people with excess body fat, a dark skin tone or older age usually need to use a moderately dosed daily vitamin D supplement, particularly those living in a high-latitude region, getting little ultraviolet B exposure due to air pollution or staying mostly indoors. Carriers of the GC (group-specific component) rs4588 AA genotype also are more likely to become deficient. Very high-dosed supplements with more than 4000 IU vitamin D are rarely needed or justified. A state-by-state Mendelian randomisation analysis of excess COVID-19 mortality of African-Americans in the USA shows a greater disparity in northern states than in southern states. It is conceivable that vitamin D adequacy denies the virus easy footholds and thereby slows spreading of the contagion. This finding should drive home the message that vitamin D supplementation is particularly important for individuals with dark skin tones. Vitamin D deficiency, even for a few months during the winter and spring season, must be rigorously remedied because of its many adverse health impacts that include decreased life expectancy and increased mortality. Slowing the spread of COVID-19 would be an added bonus.